2007
DOI: 10.1099/jmm.0.46859-0
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of hepatitis C virus infection among incarcerated Ghanaians: a national multicentre study

Abstract: A national multicentre cross-sectional study was undertaken on the correlates of hepatitis C virus (HCV) infection in a sample of inmates from eight Ghanaian prisons. A total of 1366 inmates from eight of the ten regional central prisons in Ghana were enrolled between May 2004 and December 2005. Subjects voluntarily completed a risk-factor questionnaire and provided blood specimens for unlinked anonymous testing for the presence of antibodies to HCV. These data were analysed using both univariate and multivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 22 publications
1
34
1
2
Order By: Relevance
“…34 A study that is conducted in Tehran (Iran) revealed that among the prisoners who reported no history of injecting drug use, HIV-1 prevalence has been 5.4%, and lack of condom use during sex has been significantly associated with infection (OR, 3.42). This study concluded that harm reduction programs, which have been started in Iran, should be urgently expanded particularly in correctional settings and strengthened by condom use promotion to prevent sexual acquisition or transmission of HIV-1.…”
Section: Illegal Sex and Homosexualitymentioning
confidence: 98%
“…34 A study that is conducted in Tehran (Iran) revealed that among the prisoners who reported no history of injecting drug use, HIV-1 prevalence has been 5.4%, and lack of condom use during sex has been significantly associated with infection (OR, 3.42). This study concluded that harm reduction programs, which have been started in Iran, should be urgently expanded particularly in correctional settings and strengthened by condom use promotion to prevent sexual acquisition or transmission of HIV-1.…”
Section: Illegal Sex and Homosexualitymentioning
confidence: 98%
“…La prevalencia (1,5%) fue baja en relación con los porcentajes reportados en otras cárceles de Estados Unidos, Irlanda, España, México y Brasil (6,16,17,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), y en quienes están en hemodiálisis o reciben transfusiones múltiples en Venezuela (34)(35)(36). Sin embargo, concuerda con las bajas prevalencias observadas en la población general, trabajadoras sexuales, usuarios de drogas intravenosas y donantes de este país (33,38,39), lo cual sugiere una baja circulación del virus en la región.…”
Section: Discussionunclassified
“…Se han observado altas prevalencias del virus de la hepatitis C en instituciones penitenciarias de Francia (4,9%), España (34,2% a 38,2%), Italia (38,2% a 90%), Australia (30,2% a 42%), Irlanda ((72%), Irán (45,4%), Ghana (18,7% a 19,2%), México (10%), Estados Unidos (13% a 23,1%) y Canadá (15,9% a 16,6%) (6,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). En América latina, los únicos datos publicados sobre la infección en reclusos provienen de Brasil, donde se han observado prevalencias de 4,8% a 41% (13,14,31).…”
unclassified
“…Mathematically, there is a trivial equilibrium, known as the disease-free equilibrium, which is globally asymptotically stable whenever R 0 < 1 [17]. A brief survey reveals that a number of statistical and mathematical studies for assessing the transmission dynamics of infectious diseases within correctional institutions have been proposed (see [10,[18][19][20][21][22][23][24]) to mention a few. This paper seeks to use a mathematical model to asses the impact intravenous drug misuse on the dynamics of HIV and HCV within correctional institutions.…”
Section: Introductionmentioning
confidence: 99%
“…Prison populations constitute a very high-risk group; they have high levels of HCV infection and HIV or HBV coinfection [11,12]. HCV positive inmates are at exceptional risk for coinfection with HIV because of the association of injectable substance abuse [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%